Diagnóstico de los factores de riesgo de la carga física de los trabajadores(as) de las UDIV de la carrera Agroindustria ESPAM MFL - Quijije Antón, Carmen Auxiliadora (2014)
This research was carried out with the objective of diagnosing the risk factors of physical load in the workers in units of teaching, research and the career of agribusiness of the MFL spam link (IVDU). For which it was created a procedure for a diagnosis in this context, it has five stages; the first refers to the familiarization with the area of study, where the team had direct contact with the entity to be evaluated. The second stage is the diagnosis and assessment of musculo-skeletal disorders, where could be detected through a survey the symptoms and pathologies that can generate TME highlighting the presence of backaches, neck and legs, in this same phase was the selection and application of the method of valuation of TME according to activities, using the method of REBA were assessed a total of 32 activities of which fifteen are the most relevant to causing MSDS workers and therefore they were subjected to an improvement plan to contribute to the safety, health and well-being, by means of the NIOSH method was evaluated activity grinding corn in the process of flour which complies with the limitations of this method resulting in a risk of 2.42 that long-term can generate consequences of TME. What can be concluded that an ergonomic Diagnostics within the work area can prevent any anomaly on the health of the working.